Ekosistem Industri Halal di Indonesia: Konsep, Tantangan, dan Peluang Pengembangannya - Jihan Auliya Azizah; Ratih Kirantiani; Nelis Jamjam Munawaroh (SPT. haria Journal and Education Center Publishing, 2026)
The Muslim halal industry ecosystem is an integrated system that encompasses the entire chain of activities, ranging from the production, distribution, and consumption of halal products in accordance with Islamic principles. This study aims to examine the importance of developing the halal industry ecosystem in Indonesia as a country with a Muslim-majority population and its potential to enhance global competitiveness. The research employs a qualitative descriptive approach by reviewing secondary data obtained from various relevant sources. The findings indicate that the halal industry in Indonesia has significant growth potential, supported by the large Muslim population, the increasing number of halal certifications, and the substantial contribution of halal products to the national economy. Furthermore, government support through regulations, digitalization, and collaboration among stakeholders has strengthened the national halal ecosystem. The halal industry extends beyond the food and beverage sector to include tourism, cosmetics, fashion, and Islamic finance. With optimal management, the halal industry ecosystem can increase consumer trust, stimulate economic growth, and expand the export market for Indonesian halal products at the global level.